Are all online hotel prices created dynamic? An empirical assessment. (October 2017) - Melis, Giuseppe; Piga, Claudio A.
Highlights: Dynamic pricing is a by-product of revenue management activities. It is thought to be a pervasive feature of hotels' online pricing behavior. There are also, however, theoretical reasons for implementing uniform, time-invariant prices. We track the prices of Mediterranean hotels on an Online Travel Agent, and find a strong propensity to use uniform pricing. Such a propensity falls sharply in 4 and 5 star hotels, which represent, however, a small proportion in all markets. The use of revenue management techniques appears to be correlated with the company's culture and its organizational design. Abstract: Understanding how tourist firms set their online prices is important given their growing reliance on Online Travel Agencies (OTA). The article investigates whether the narrative of a pervasive presence of dynamic pricing provides a realistic description of hotels' online pricing behavior and thus challenges the view that dynamic pricing should be considered the prevailing norm for the industry. The evidence suggests a heterogeneous attitude across hotels, with uniform pricing being more widespread in most hotels of our sample, namely, the 3-star or less, while dynamic pricing is more likely applied in higher quality hotels.